Organ-, inflammation- and cancer specific transcriptional fingerprints of pancreatic and hepatic stellate cells - Erkan, Murat Mert; Weis, Nadine; Pan, Zheng; Schwager, Christian; Samkharadze, Tamar; Jiang, Xiaohua; Wirkner, Ute; Giese, Nathalia; Ansorge, Wilhelm; Debus, Jürgen; Huber, Peter E.; Friess, Helmut; et al. (Molecular cancer, 2010)
Tissue fibrosis is an integral component of chronic inflammatory (liver and pancreas) diseases and pancreatic cancer. Activated pancreatic- (PSC) and hepatic- (HSC) stellate cells play a key role in fibrogenesis. To identify organ- and disease-specific stellate cell transcriptional fingerprints, we employed genome-wide transcriptional analysis of primary human PSC and HSC isolated from patients with chronic inflammation or cancer.